2008
DOI: 10.1056/nejmoa0800390
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent Type 1 Oral Poliovirus Vaccine in Newborns

Abstract: When given at birth, monovalent type 1 oral poliovirus vaccine is superior to trivalent oral poliovirus vaccine in inducing humoral antibodies against type 1 poliovirus, overcoming high preexisting levels of maternally derived antibodies, and increasing the resistance to excretion of type 1 poliovirus after administration of a challenge dose. (Current Controlled Trials number, ISRCTN76316509.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 17 publications
2
50
1
Order By: Relevance
“…The design of the study of the comparative immunogenicity of mOPV1 versus tOPV has been described previously (15). Briefly, 530 newborns from three sites in Egypt located in Greater Cairo and Alexandria were randomly distributed into two groups (A and B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of the study of the comparative immunogenicity of mOPV1 versus tOPV has been described previously (15). Briefly, 530 newborns from three sites in Egypt located in Greater Cairo and Alexandria were randomly distributed into two groups (A and B).…”
Section: Methodsmentioning
confidence: 99%
“…In 2005/2006, a clinical study was conducted in Egypt to compare the immunogenicity of mOPV1 with that of the tOPV in newborns (15). Newborns were vaccinated with mOPV1 or tOPV as soon as possible after birth and were challenged with mOPV1 4 weeks later.…”
mentioning
confidence: 99%
“…Most of these substitutions are synonymous (d n /d s ϭ 0.03, where d n is the rate of nonsynonymous substitutions and d s is the rate of synonymous substitutions) (8). However, previous studies have indicated that in Sabin strains, reversion of known attenuating sites can occur within the duration of a single infection and that VP1 substitutions accumulate more quickly than would be expected from the wild-type neutral substitution rate; multiple VP1 substitutions occur within the first month after administration of the vaccine dose (10)(11)(12)(13)(14)(15). In addition, most reported cVDPV isolates are recombinants with Sabin-derived capsid and enterovirus C (poliovirus and nonpoliovirus) noncapsid sequences, although the role of selection pressure in this process is not clear (1,2,11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…For that reason, the Endgame Strategy aims for global cessation of type 2 OPV by switching from trivalent to bivalent OPV in routine immunization programs [53]. Such bivalent vaccines (type 1 and 3) are more immunogenic than trivalent OPV [54] and nearly as effective as the monovalent OPV formulations, especially in young children receiving their first polio immunization [55][56][57][58]. However, the risks of VAPP and vaccinederived polioviruses by reversion of the Sabin strains to a pathogenic strain still remain, and thus the global eradication of polio by using these OPVs is impossible.…”
Section: Opvmentioning
confidence: 99%